Keys to the Ethiopian tribes and genera of the sub-families Ponerinae and Cerapachyinae with a synonymic list and general notes on the various genera (Hymenoptera : Formicidae) - Prins, A. J (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.Agric.) -- University of Stellenbosch, 1975.